PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP IBNU SINA SANGATTA UTARA - Hanifa Yuniarti; Eka Widyanti (Al-Rabwah, 2023)
This study aims to determine how much influence the Jigsaw learning model has on students' learning interest in PAI subjects at North Ibnu Sina Sangatta Middle School. The population in this study were all 31 students in class VIII because the population was less than 100 people. The results of the regression equation constant value (a) is 16,888 and (b) the jigsaw learning model is 0.644, so it can be seen that the simple linear regression model is: Y = 16,888 + 0.644. Based on the results of the hypothesis test from the t-test, it results that the Jigsaw learning model has a t-count of 4,906 with a significance level of 0.000 and therefore the t-count is greater than the t-table, namely 4,906 > 1,695, and a significance value of 0.000 <0.05, so Ha is accepted, thus the learning model Jigsaw (X) effects on students' interest in learning. (Y) in PAI subjects at the North Ibn Sina Sangatta Middle School. This means that the influence of the Jigsaw learning model on students' interest in Islamic education in class VIII SMP Ibnu Sina Sangatta Utara is 45.4%, while 54.6% is influenced by other factors.